PENGARUH PENGANGGARAN PARTISIPATIF TERHADAP KELONGGARAN ANGGARAN DENGAN ASIMETRI INFORMASI DAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA RUMAH SAKIT SWASTA DI PEKANBARU) - Ivo Daniel Tambunan; Kirmizi Ritonga; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of participative budgeting to budgetary slack with information asymetry and locus of control as moderated variabels.The research was conducted at private hospital on Pekanbaru with 70 middle managers and low managers, level of the head, head of division, the head field, the head of sub division, and the head of the sub field as a sample. The data was collected by distribution questionnaires to 15 private hospital with data analysis techniques use are Moderated Regression Analysis (MRA) with SPSS 20 for windows.From the result of multiple regression that participative budgeting having a significant effect on budgetary slack, while information asymetry does not significant effect relationship of participative budgeting with budgetary slack, and locus of control having a significant effect relationship of participative budgeting with budgetary slack. The magnitude effect (R2) by these three variabels together to the dependent variabels is equal to 67,80%, while remining 32,30% is effected by the others variabels not examined in this study.Keywords: Participative Budgeting, Information Asymetry, Locus of Control, and Budgetary Slack.